A STRESS-FREE APPROACH TO TEFL - Ahsani, Nizam (Kajian Linguistik dan Sastra, 2007)
The teaching of English in Indonesia has been marked with the frequent changesin the curriculum. However, those changes do not imply whatsoever any changesin the way teachers deliver lessons in a moment-to-moment classroom teaching.We seem to be too much preoccupied with new concepts and perhaps approach toteaching English but fail to formulate how a certain concept can be translated intoclassroom methods and techniques. This paper seeks to shed a light on how a synthesisof various approaches in language learning can be achieved to provide favorablelearning atmosphere for students and more importantly how different theorieson language learning can be transformed into an operational method andtechniques in the classroom.